Motivasi sebagai Faktor Determinasi Prestasi Kerja Pegawai di Sekretariat Daerah Kabupaten Minahasa Utara - Florence Daicy Jetty Lengkong (Jurnal Aplikasi Manajemen, 2010)
The purpose of this study is to understand the effect of work motivation to the employees achievement. This research is included in to the explanatory research, and the unit analysis that is the individual and research sample is represented by the Regent Office of North Minahasa based on the sratified random sampling. The methods of analysis used are the descriptive and statistic inferential which is simple linear regression analysis. This research indicated that motivation have positive impact and significant lo the employees achievement at the Regent Office of North Minahasa. Therefore, that motivation represent is very important factor and have to be paid attention by the leader to find out the employee’s achievement now and forever.